Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1365-2389.2009.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate dependence of heterotrophic soil respiration from a soil‐translocation experiment along a 3000 m tropical forest altitudinal gradient

Abstract: Summary Tropical ecosystems play a key role in the global carbon cycle, but their response to global warming is not well understood. Altitudinal gradients offer the unique possibility of undertaking in situ experimental studies of the influence of alterations in climate on the carbon (C) cycle. In a soil‐translocation experiment we took replicate soil cores at 3030 m, 1500 m, 1000 m and 200 m above sea level along an altitudinal gradient in tropical forest in Peru, and exchanged (i.e. translocated) them among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 57 publications
(83 reference statements)
5
99
1
Order By: Relevance
“…Therefore, Q 10 was mainly affected by transfer of the soils. Although different methods used to calculate Q 10 might lead to different results (Zimmermann et al 2009), Q 10 calculated by use of both the van't Hoff (the most commonly used equation) and the Lloyd and Taylor (suggested to give an unbiased estimate of Q 10 ) equations had consistent responses to the treatments in our study.…”
Section: Labile Organic Carbonmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, Q 10 was mainly affected by transfer of the soils. Although different methods used to calculate Q 10 might lead to different results (Zimmermann et al 2009), Q 10 calculated by use of both the van't Hoff (the most commonly used equation) and the Lloyd and Taylor (suggested to give an unbiased estimate of Q 10 ) equations had consistent responses to the treatments in our study.…”
Section: Labile Organic Carbonmentioning
confidence: 75%
“…In addition, if we do not consider the direction of soil monolith transfer, both high and lowelevation soils had 44 % greater CO 2 flux when they were incubated in the low-elevation site than those incubated in the high-elevation site, indicating that the temperature difference between the two sites determined the different CO 2 flux rates. In combination with higher soil C stock at the higher-elevation site (Table 1), similar CO 2 flux rate between both soils incubated in situ implies that more C would be stored in the soil at the high-elevation site (Zimmermann et al 2009(Zimmermann et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further descriptions of soil properties (Quesada et al 2010;Whitaker et al 2014;Zimmermann et al 2009), climate (Rapp and Silman 2012) and aboveground productivity and floristic composition (Asner et al 2013;Feeley et al 2011;Girardin et al 2010) for these sites are reported elsewhere.…”
Section: Study Sitesmentioning
confidence: 99%
“…However, there was no significant relation detected between soil respiration and temperature [14]. Similarly, in a study on climate dependence of heterotrophic soil respiration along a 3000-m elevation gradient in a tropical forest in Peru, Zimmermann et al (2009) also concluded that the soil respiration rate did not vary significantly along the elevation gradient with decreasing temperature, although SOC stocks increased linearly with increased elevation [17].…”
Section: Discussionmentioning
confidence: 99%